Ejercicios de estabilización del Core en mujeres gestantes con dolor lumbopélvico. - Cazar Bonilla, Alejandra Estefania (2024)
Core stabilization exercises in pregnant women with lumbopelvic pain, addresses a common manifestation during pregnancy, significantly affecting the quality of life; therefore, it is intended to demonstrate the effectiveness of Core stabilization exercises to demonstrate the impact it has on reducing pain by strengthening and stability of the muscles in order to reduce the pain generated by the pressure exerted on the back and pelvis during pregnancy. Methodology: The research design was documentary, in which searches were conducted in databases such as: Scielo, Scopus, Pubmed, Web Of Science, among others, with the help of Boolean operators (AND & OR). The type of bibliographic study focused on a qualitative approach with a descriptive level, to specify the presence and decrease of pain according to the intensity and frequency in pregnant women; by means of the inductive method, the effectiveness of the intervention was determined. Results: A total of 306 articles focused on studies on Core stabilization exercises in pregnant women with lumbopelvic pain were found, in which inclusion and exclusion criteria were applied since 2011 due to the lack of updated information, selecting a final sample of 25 articles. Conclusion: Core stability exercises help to reduce pain and functional disability in pregnant women. From the different articles analyzed, it was possible to conclude that resistance and strength exercises are safe and beneficial for pregnant women without increasing the probability of musculoskeletal injuries, as long as they are professionally supervised interventions.